Public policies and competitiveness in the pharmaceutical industry: The case of Brazil and India - Franculino, Kleber Alves da Silva [UNESP]; Gomes, Rogério [UNESP] (My University, 2017)
This study aims to evaluate how public policies adopted by Brazil and India in past decades have influenced the development of the pharmaceutical industry in these countries. The industry performance is measured by international trade indicators, from 1995 to 2011, to capture the effects of the adoption of the TRIPS Agreement on the productive structure of medicines. Two hypothesis are assumed: international trade flows may express aspects of the industry competitiveness; and the success of these public policies implicates in increased competitiveness. The results indicate that the continuity of the policies is crucial to explain the differences of industry competitiveness in both countries.
Keywords: Brazil; Competitiveness; India; Pharmaceutical industry; Public policies